Roald Dahl's book of ghost stories. - Dahl, Roald (New York : Farrar, Straus, Giroux, 1983)
A collection of ghost stories.
W.S. -- Harry -- The corner shop -- In the tube -- Christmas meeting -- Elias and the Draug -- Playmates -- Ringing the changes -- The telephone -- The ghost of a hand.
Young Adult
Young Adult
Horn Book
Keywords: Ghost stories, American; Ghost stories, English; Ghost stories